ELECTORAL SYSTEM FOR POST-WAR UKRAINE: CURRENT ALTERNATIVES FOR PARLIAMENTARY ELECTIONS - Avksentiev, Anton (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
This study examines the issue of selecting an optimal electoral system for the first post-war elections to the Verkhovna Rada. It argues that the design of the electoral system will have a significant impact on both the representativeness and institutional capacity of the parliament. The article traces the evolution of Ukraine’s electoral system and reviews specific electoral models applied in parliamentary elections from 1994 to 2019. It substantiates that the model currently enshrined in the Electoral Code constitutes a system with «flexible» (or «semi-open») rather than fully «open» lists. Four types of electoral systems are identified as relevant alternatives for organizing the first post-war parliamentary elections: proportional representation with closed lists, a parallel mixed system, a two-tier proportional system with flexible regional lists (as defined by the current Electoral Code), and its modified version proposed in Draft Law №13464. A comparative analysis of these models is conducted using 10 key evaluation criteria. The findings support the appropriateness of retaining the current system as the foundation for post-war parliamentary elections. The study draws not only on theoretical insights but also on empirical data from the implementation of this system in the 2020 local elections. The analysis of this experience has led to practical recommendations for transforming the current model into a fully open-list system. Such a transition is expected to enhance the role of preferential voting by citizens and reduce the degree of party leadership control over the allocation of mandates. These recommendations align with data from sociological and expert surveys, highlighting public support for «open lists». The study’s conclusions may serve as an analytical basis for improving electoral legislation and making informed decisions regarding the electoral system during the transitional post-war period. Prospects for further research are outlined, with an emphasis on ensuring the full participation of overseas voters in shaping the personal composition of parliament.